Influence of Organic Matter and Speciation on the Dynamics of Trace Metal Adsorption on Microplastics in Marine Conditions - Ana Rapljenović; Marko Viskić; Stanislav Frančišković-Bilinski; Vlado Cuculić (Toxics)
Dissolved organic matter (DOM), primarily in the form of humic acid (HA), plays a crucial role in trace metal (TM) speciation and their subsequent adsorption dynamics on microplastics (MP) in aquatic environments. This study evaluates the impact of environmentally relevant concentrations of HA on the adsorption behaviors of essential (Co, Cu, Ni, and Zn) and toxic (Cd and Pb) TMs onto polyethylene (PE) and polypropylene (PP) pellets, as well as PP fibers under marine conditions, during a six-week experiment. The HA concentrations were 0.1, 1, and 5 mg/L, while all metals were in the same amounts (10 µg/L). Results reveal that HA significantly influences the adsorption of Cu, Pb, and Zn on MP, particularly on PP fibers, which exhibited the greatest TM adsorption dynamics. The adsorption patterns correspond to the concentrations of these metals in seawater, with the sequence for pellets being Zn > Cu > Pb > Ni > Co~Cd, and for fibers Cu > Zn > Pb > Co~Ni > Cd. Speciation modeling supported these findings, indicating that Cu, Pb, and Zn predominantly associate with HA in seawater, facilitating their adsorption on MP, whereas Cd, Co, and Ni mainly form free ions and inorganic complexes, resulting in slower adsorption dynamics. Statistical analysis confirmed the influence of HA on the adsorption of Cd, Pb, Cu, and Ni. By investigating the dynamics of TM adsorption on plastics, the influence of DOM on these two contaminants under marine conditions was evaluated. The presented results can help in forming a better understanding of synergistic plastic and trace metal pollution in marine systems that are relevant at the global level, since both contaminants pose a serious threat to aquatic ecosystems.